Peningkatan Pengetahuan dan Keterampilan Siswa Jurusan Akuntansi Melalui Pengenalan Akuntansi Berbasis Digital di SMK Negeri 2 Tegal - Aryanto, Aryanto; Farida, Ida; Maulidah, Hikmatul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Students majoring in accounting need to be equipped with the knowledge and skills to operate digital accounting applications. The implementation of this service activity is located at SMK Negeri 2 Tegal with the aim of increasing knowledge about digital-based accounting and increasing skills in operating digital-based accounting applications for students at SMK Negeri 2 Tegal. The method of implementing this community service activity is the lecture method, guidance, and ends with a question and answer discussion. The material for community service activities includes the introduction of digital-based accounting applications, the practice of operating applications by working on case exercises, and closing with the final results of the activity. The results of this community service activity are increasing students' knowledge and skills in operating digital-based accounting applications, so that they can be used as capital knowledge for students when they graduate.